Kompetisi dan Strategi Pengembangan Lembaga PAUD Islam Berdaya Saing di TK Islam Al-Irsyad Banyumas - Novan Ardy Wiyani (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
This article is aimed at describing the competition as well as the development strategy of the Islamic Kindergarten “Al-Irsyad” as one of competitive Islamic early childhoodeducation institution in Purwokerto. The purpose is to find the pattern of the developmentstrategy of the competitive Islamic early childhood education institution. This sort ofinstitution is expected to be able to compete in achieving righteousness in line with Islamicteachings dedicated to the community. This can be done if the Islamic early childhoodeducation institutions promote competitive excellent service. Furthermore, the rationalelies behind the idea of competitive Islamic early childhood education institutions is togenerate competitive advantage within Islamic early education institutions, to improvecommunity’s loyalty as served customer, to create Islamic early childhood institutionswhich are able to outweigh their competitors while at the same time upholding ethics,as well as Islamic virtues.